Plastic Waste as Cement Replacement in Brick Application - Bin Ismail , Ahmad Iqbal Khairi (Universiti Teknologi PETRONAS, 2018)
Cement is a basic component in construction that can never be separated and its usage are increasing year by year due to high demand in the building development. Most of the plastics are not biodegradable and an enormous of plastic waste are increasing worldwide. Both plastics and cement are harmful to the environment and can lead to the pollution toward the earth. This study aim to reduce the usage of cement in construction industry and reduce the plastic waste by recycling it into bricks. The objective of this study are to find suitable treatment for plastic as a binder, to find the formulation of brick using plastic as a binder, and lastly to test the brick. The treatment used to turn plastic into a binder is heat, the plastic waste is heated until it is melt and the river sand is added and mixed together with plastic waste. Five samples are made to find the best formulation of plastic brick using plastic waste and river sand, 10 %, 20 %, 30 %, 40 % and 50 % of plastic waste are used to produce the samples. All five samples are tested for the compression, water absorption, thermal conductivity and fire resistance. Sample with 40 % of plastic waste obtained the highest compressive strength which is 21.72 MPa and sample with 10 % of plastic waste obtained the lowest 4.4 MPa. For the water absorption test only sample with 10 % of plastic waste exceed 1 % of water absorption which is 4.40 % while the other samples are below 1 % which are 0.70 %, 0.64 %, 0.06 % and 0 %. For thermal conductivity test, all the samples obtained less than 1 W/m which are 0.8117, 0.2185, 0.8066, 0.1158, and 0.3761 W/m. Sample with 10 % of plastic waste obtained the longest time during fire resistance test which is 758 s while the shortest time is sample with 50 % plastic waste which is 501.5 s. Sample with 10 % of plastic waste can be used as common building brick as it compressive strength is 4.4 MPa which is in between 3.5 – 6.8 MPa while the other samples can be used as first class brick as the compressive strength is higher than 10.3 MPa and water absorption is lower than 20 %. For the conclusion; heat is a suitable treatment to treat plastic as a binder, the best formulation of brick is 40 % HDPE, and lastly all the brick sample were successfully tested with compressive strength, water absorption, thermal conductivity and fire resistance test.